Effect Of Product Quality,Perceived Priceand Brand Image On Purchase Decision Mediated By Customer Trust (Study On Japanese Brandelectronic Product) - Lily Suhaily; Syarief Darmoyo (Jurnal Manajemen, 2017)
Today the economic growth in many parts of the world has increased, especially in developing country, such Indonesia country. With increased economic growth, income and purchasing power of consumers also increased especially in big city like Jakarta. Increased incomes allow consumers to meet their secondary and tertiary needs such air conditioning (AC), washing machine, refrigerator with advanced technology. The purpose of this study was to determine the effect of product quality, perceived price and brand image of the brand purchase decision on Japan's electronics are mediated by consumer trust. Population of this research is visitors of electronic city outlet in South Jakarta and questionnaires were distributed to 376 visitors Electronics City in SCBD and in Pondok Indah Mall using multistage cluster random sampling technique. Data were analyzed using Structural Equation Modeling ( SEM ). The results showed that there are product quality and perceived price have significant and positive effect of the purchase decision; product quality, brand image and perceived price have significant and positive effect of the customer trust; customer trust has significant and positive effect of the purchase decision; no effect of brand image of purchase decision;Â  product quality, perceived price and brand image of the purchase decision mediated by consumer trust in electronic products of Japanese brand